Challenges in Higher Education for Sustainable Development - Dr. S. Kumar (South Eastern European Journal of Public Health, 2025)
The sustainable development in higher education, highlighting its growing importance in the face of global environmental and social challenges. This background information sets the stage for the study's relevance and significance. The primary objective of the study should be clearly articulated, focusing on the identification and analysis of challenges in implementing sustainable development principles within higher education institutions. A concise description of the research methodology employed in the study is crucial for establishing the credibility and rigor of the findings. The principal findings of the research should be summarized, highlighting the main challenges identified in implementing sustainable development in higher education. These challenges may encompass a range of issues, such as insufficient institutional support for sustainability initiatives, constrained resources and funding for sustainable projects, difficulties in integrating sustainability concepts into existing curricula, resistance to change from faculty and administrative staff, and inadequate awareness and comprehension of sustainability concepts among various stakeholders. The abstract should also discuss the implications of these challenges on achieving sustainable development goals in higher education. This may include the potential impact on student learning outcomes, institutional operations, and the broader societal role of universities in promoting sustainability. In conclusion, the researcher should present a succinct statement on the importance of addressing these challenges and suggest potential avenues for future research or action. This may include recommendations for policy changes, innovative educational approaches, or further studies to deepen understanding of the issues identified.